Different Proteomics of Ca2+ on SA-induced Resistance to Botrytis cinerea in Tomato - Linlin Li; Peng Guo; Hua Jin; Tianlai Li (Horticultural Plant Journal, 2016)
This study aims to comprehensively study the effects of Ca2+ on the SA-induced resistance Botrytis cinerea in tomato through proteomics analysis. A proteomic approach was used to uncover the inducible proteins of tomato in the susceptible tomato cultivars ‘L402’ against Botrytis cinerea after salicylic acid (SA) and a combination treatment of CaCl2 and SA. The results showed that the use of combination treatment of CaCl2 and SA significantly enhanced tomato resistance against Botrytis cinerea. In total, 46 differentially expressed protein spots from 2-DE gel maps were detected, of which 41 were identified by mass spectrometry. All the identified proteins were categorized into eight groups according to their putative functions: defense response (14.00%), antioxidative protein (9.75%), photosynthesis (24.39%), molecular chaperone (4.88%), energy (17.01%), metabolism (21.95%), protein synthesis (4.88%) and signal transduction (0.2%). Of the proteins in the eight function groups, the effect of stress/defense and reactive oxygen species on Ca2+-regulated SA-induced resistance may be the most important one in induced resistance by RT-PCR. The expression level of pathogenesis-related proteins (PRs) and chitinase was upregulated by a combination treatment of CaCl2 and SA. The characterization of these proteins greatly helped to reveal the induced proteins involved in the regulation of Ca2+ on SA-induced resistance to Botrytis cinerea. In the combination treatment of CaCl2 and SA, the defense response and antioxidative protein were clearly upregulated much more than SA alone or the control treatment by the method of proteomics and RT-PCR. The present findings suggest that susceptible tomato cultivars treated by the combination treatment of CaCl2 and SA might possess a more sensitive SA signaling system or effective pathway than SA treatment alone. In addition, results indicated that SA could coordinate other cellular activities linked with photosynthesis and metabolism to facilitate defense response and recovery, indicating that the self-defense capability of tomato was improved by the combination treatment of CaCl2 and SA.